Lithuania and Italy Economic Relations in the Interwar Period: Changes and Tendencies - Užusėnaitė, Rugilė (Vilnius University Open Series, 2021)
The aim of this article is to study the economic cooperation between Lithuania and Italy during the interwar period and to see the peculiarities of the relations under discussion. The economic cooperation of the countries in question is understood here as the exchange of various goods and products – export and import data are analysed. The passivity of Lithuania and Italy economic cooperation ended at an early stage by the Lithuanian – Italian trade agreement signed in 1927, which guaranteed the application of the most favourable trade. Thanks to this agreement Lithuania and Italy export and import with certain exceptions had an upward trend until 1935. On the other hand, Lithuania had a negative trade balance with Italy until 1939 and the trade turnover of both countries had never reached more than 3 percent of Lithuania’s total foreign trade turnover. Further trade prospects were interrupted by the Second World War.
Keywords: Lithuania and Italy; foreign trade; economic cooperation; export and import; trade agreement